If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + -1) + 15 = 7 Reorder the terms: 3x(-1 + x) + 15 = 7 (-1 * 3x + x * 3x) + 15 = 7 (-3x + 3x2) + 15 = 7 Reorder the terms: 15 + -3x + 3x2 = 7 Solving 15 + -3x + 3x2 = 7 Solving for variable 'x'. Reorder the terms: 15 + -7 + -3x + 3x2 = 7 + -7 Combine like terms: 15 + -7 = 8 8 + -3x + 3x2 = 7 + -7 Combine like terms: 7 + -7 = 0 8 + -3x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 2.666666667 + -1x + x2 = 0 Move the constant term to the right: Add '-2.666666667' to each side of the equation. 2.666666667 + -1x + -2.666666667 + x2 = 0 + -2.666666667 Reorder the terms: 2.666666667 + -2.666666667 + -1x + x2 = 0 + -2.666666667 Combine like terms: 2.666666667 + -2.666666667 = 0.000000000 0.000000000 + -1x + x2 = 0 + -2.666666667 -1x + x2 = 0 + -2.666666667 Combine like terms: 0 + -2.666666667 = -2.666666667 -1x + x2 = -2.666666667 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = -2.666666667 + 0.25 Reorder the terms: 0.25 + -1x + x2 = -2.666666667 + 0.25 Combine like terms: -2.666666667 + 0.25 = -2.416666667 0.25 + -1x + x2 = -2.416666667 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = -2.416666667 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 40+2y-16=11y-11-4y | | 1223423123x=213123123 | | -3x+18=-10x+4 | | 3x+9=5x-19 | | 6(2.5)+3y=12 | | (3x)(3x-2)(x)=540 | | 0=0.3x^2+2x-50 | | x-55=10 | | 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) | | 21-x=28 | | n-n*n=72 | | 4(a+9)=7[a-(3-a)] | | 9x^2=50x-25 | | 4x-7=36 | | x^3-5x^2+4x-2=0 | | 42x=35x+70 | | 6(4n-4)=-60 | | 8-2n=40 | | 7x+7=-5x+43 | | 49s^2-14s+1=0 | | 8k^2-20=-9k | | 5(7+2)=x-11 | | x-0.4=4.2 | | f(x)=ln(6x) | | 4x+5y+4=0 | | Cos(5x)-cos(3x)=0 |